(untitled) (Journal of Management and Social Sciences, 2026)
Globally, strained relationships among people from different religious backgrounds bring diverse negative consequences, and it is a concern for many people. While literature abounds on it, few have studied it from the perspective of the lived experiences of the people. Therefore, this study adopted the phenomenology method to study strained interreligious relationships in Osun State, Nigeria. The instrument for the study was an In-depth Interview Guide, and the interviews were conducted with 30 purposively selected respondents from Iwo and Ilesa West Local Government Areas of the State. The respondents comprised 15 religious clerics and 15 laity, among whom were eight African Traditional Religion adherents, 10 Christians, and 12 Muslims. The study revealed four groups of factors that explained causes of strained interreligious relationships: individual-based, government-based, religion-based, and community-based factors. Individual-based factors include religious stereotypes and the fear of communicating with adherents of other religions. Government-based factors include blurred legal boundaries for exercising religious rights and freedom, perceived religiously-biased legislation and policies, and discriminatory behaviours of some government workers. Religion-based factors include perceived inappropriate and harmful religious practices, and community-based factors include a lack of or ineffective community associations. The paper recommends a four-dimensional approach to mitigating strained interreligious relationships in the state. Keywords Interreligious, Christians, Muslims, African Traditional Religion, Nigeria, interfaith